Endoscopic band ligation in the treatment of gastric antral vascular ectasia: a systematic review and meta-analysis - McCarty, Thomas R.; Hathorn, Kelly E.; Chan, Walter W.; Jajoo, Kunal (Endoscopy International Open, 2021)
Background and study aims While argon plasma coagulation (APC) is the first-line treatment for gastric antral vascular ectasia (GAVE), endoscopic band ligation (EBL) has shown promising results. The aim of this study was to perform a systematic review and meta-analysis to evaluate the effectiveness of EBL for the treatment of GAVE.Methods Individualized search strategies were developed in accordance with PRISMA and MOOSE guidelines through September 1, 2020. Measured outcomes included endoscopic success (defined as GAVE eradication/improvement), change in hemoglobin, transfusion dependency, number of treatment sessions, adverse events, rebleeding, and bleeding-associated mortality. Outcomes were compared among studies evaluating EBL versus APC.Results Eleven studies (n = 393; 59.39 % female; mean age 58.65 ± 8.85 years) were included. Endoscopic success was achieved in 87.84 % [(95 % CI, 80.25 to 92.78); I2 = 11.96 %] with a mean number of 2.50 ± 0.49 treatment sessions and average of 12.40 ± 3.82 bands applied. For 8 studies comparing EBL (n = 143) versus APC (n = 174), there was no difference in baseline patient characteristics. However, endoscopic success was significantly higher for EBL [OR 6.04 (95 % CI 1.97 to 18.56; P = 0.002], requiring fewer treatment sessions (2.56 ± 0.81 versus 3.78 ± 1.17; P < 0.001). EBL was also associated with a greater increase in post-procedure hemoglobin [mean difference 0.35 (95 % CI 0.07 to 0.62; P = 0.0140], greater reduction in transfusions required [mean difference –1.46 (95 % CI –2.80 to –0.12; P = 0.033], and fewer rebleeding events [OR 0.11 (95 % CI, 0.04 to 0.36); P < 0.001]. There was no difference in adverse events or bleeding-associated mortality (P > 0.050).Conclusions EBL appears to be safe and effective for treatment of GAVE, with improved outcomes when compared to APC.